Global Business Strategy Multinational Corporations Venturing into Emerging Markets - Motohashi, Kazuyuki; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2015)
This book presents theories and case studies for corporations in developed nations, including Japan, for designing strategies to maximize opportunities and minimize threats in business expansion into developing nations. The case studies featured here focus on Asia, including China and India, and use examples of Japanese manufacturers. Five case studies are provided, including Hitachi Construction Machinery and Shiseido in China and Maruti Suzuki in India. These cases facilitate the reader$1 (Bs understanding of the business environments in emerging economies. This volume is especially recommended for businesspeople responsible for international business development, particularly in China and India. In addition, the book serves as a useful resource for students in graduate-level courses in international management.s
1. Introduction: Needs for New Global Strategies -- Part I. Global Business Strategy -- 2. Management Strategies for Global Businesses -- 3. Changes in the Global Economic Environment -- 4. Comparison of Economic Institutions in China and India -- 5. New Business Model as Response to Competition from Emerging Economies -- 6. India$1 (Bs Neemrana Industrial Park for Japanese Firms -- Part II. Fundamentals Of Strategic Planning -- 7. Alliance-based Global Strategy -- 8. Hitachi Construction Machinery: Becoming a Wholly Owned Chinese Entity -- 9. Marketing Theory in Global Business Context -- 10. Shiseido Marketing in China -- 11. International R&D Management -- 12. Multinationals$1 (BR&D in China and India -- 13. Thailand$1 (Bs National Science and Technology Development Agency and Japanese Firms -- 14. Suzuki Motor$1 (Bs Expansion in India -- 15. Strategy Integration at the Global Level.s
Keywords: International economic integration; Globalization; Technological innovations; Strategic planning; Leadership; International economic relations; Production management; Emerging Markets and Globalization; Innovation and Technology Management; Business Strategy and Leadership; International Economics; Operations Management